Retail Buyer and Manufacturer Influence - Subramanian, Upender; Zhang, Z. John (Management Science, 2024)
Retailers often employ professionals known as retail buyers to determine the right quantities of products to order. However, in many economies and industries, a manufacturer may seek to unduly influence the buyer through various means. One such means is to offer the buyer kickbacks (incl. entertainment, travel, gifts) in return for a large order. Despite prominent examples of retailers taking initiatives against kickbacks, the practice persists in many economies and industries. To aid initiatives combating kickbacks, one needs to do the right diagnosis and identify the root cause. To this end, in this paper, we introduce the retail buyer as a distinct player in the retail channel and study the implications of the tug-of-war between the retailer and the manufacturer to influence the buyer. Interestingly, we find when kickbacks are feasible, the manufacturer need not always benefit, and the retailer need not always be the victim. We show a well-designed buyer compensation plan is key for the retailer to avoid kickbacks from distorting the buyer’s demand assessments. Moreover, when the reputational harm from kickbacks is not too high, the retailer may be the one tacitly facilitating kickbacks by undercompensating the buyer and influencing her demand assessments such that it can leverage kickbacks for shifting some of its buyer compensation cost to the manufacturer. This sharing of cost may allow for better channel coordination. Furthermore, this cost-shifting mechanism of kickbacks we have identified in this paper can explain their persistence. No retailer tolerates kickbacks when the reputational harm is high. This paper was accepted by Eric Anderson, marketing. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2021.01646 .